SOCIAL JUSTICE THROUGH RESERVATIONS IN INDIA - A CONSTITUTIONAL ANALYSIS. - K.S. Gopalakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The reservation system in India aims to end caste discrimination and inequalities, promoting social upliftment and representation for the weaker sections of society. It consists of positive discrimination policies utilized by the government to help the weaker section to access employment and education in India. Sub-classification and internal reservation within the reserved categories aims to uplift the people who are not able to avail the benefits along with other communities within the reservation of common parlance of their reserved category. The paper aims in addressing the concept of social justice through reservations in India by highlighting the constitutional mandate for reservation and analysing the internal or reservation within reservation policies. The concept of creamy layer is critically analysed in order to ensure social justice within the backward classes and finally the paper suggests the pro-active measure for ensuring proper reservation in India.